PERSPEKTIF GENERASI MILENIAL TERHADAP PANCASILA - Olga Sancaya Permatasari; Margaretha Hanita (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
The purpose of this study is to find out more closely the millennial generation'sperspective on Pancasila. The founding fathers formulated Pancasila, which aims to direct the nation to achieve its goals and become an inclusive nationality. The position of Pancasila as a source of identity, personality, morality, and the course of national safety. Pancasila is one of the essential components in the concept of National Resilience in ideology that provides directions and guidelines for achieving national goals, namely the nation's survival and state. However, the fact is that the Pancasila Ideology position is now increasingly being forgotten by the Indonesian people, including the millennial generation with a large population. In the future, it will become the next generation. The fading of the appreciation and practice of Pancasila values is partly due to the various challenges facing the Indonesiannation. The method used is qualitative research with Conventional Content Analysis (CCA), the subject of this research is the millennial generation who live in DKI Jakarta. The results of this study are six categories describing the views of the millennial generation towards Pancasila, including: (1) Guidelines; The urgency of deepening Pancasila; (3) Interests; (4) The problem of understanding the values of Pancasila with two subcategories, namely language and no concrete examples; (5) Pancasila is synonymous with government; (6) Adaptive.